Proposal for a Data Model for a Multipurpose Cadastre in Chile Based on Land Administration Model ISO 19152 for Natural Disaster and Risk Management - Flores-Rozas, D (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
The mitigation of natural hazards is a persistent challenge in Chile, where recurrent events such as summer forest fires and winter floods cause severe material and human losses. Municipalities, as key actors in disaster management, often face difficulties due to fragmented territorial information and the lack of standardized tools to support decision-making. This study applies the Land Administration Domain Model (ISO 19152) International Standard to design a multipurpose cadastre adapted to the Chilean context. The methodological approach integrates cadastral data with hazard and risk information, structuring it into standardized sub-packages that facilitate spatial analysis, interoperability, and municipal planning. The proposed model demonstrates its capacity to identify risk-prone areas, link property units with hazard data, and generate reliable inputs for disaster risk reduction plans. A prototype decision-support panel illustrates how the integration of cadastral and risk data can improve access to territorial information and support local governance. The contribution of this research is twofold: first, it establishes a standardized framework for territorial information management based on ISO 19152; second, it provides municipalities with a practical tool to strengthen disaster preparedness and response, promoting more resilient and sustainable communities.